Case report: Familial hypoparathyroidism with elevated parathyroid hormone due to an inactivating PTH mutation - Mukhtar, Noha; Alghamdi, Balgees; Alswailem, Meshael; Alsagheir, Afaf; Alzahrani, Ali S. (Frontiers in Endocrinology, 2024)
Introduction: Only 11 PTH mutations have been described as causes of familial isolated hypoparathyroidism (FIH). In this report, we describe a family with FIH but with significant elevation of functionally inactive PTH due to a PTH mutation. We also show a positive therapeutic outcome of recombinant human PTH (teriparatide) therapy in one of the siblings who was not well controlled on large doses of calcitriol and calcium replacement therapy.The proband is a 34-year-old lady who has a history of chronic severe hypocalcemia (HypoCa) since birth. She and her three brothers (33-year-old male twins, and a 21year-old male) were diagnosed with pseudohypoparathyroidism type 1b (PHPT 1b) based on the presence of chronic HypoCa (serum Ca 1.6-1.85 mmol/l) since birth associated with significantly elevated plasma PTH levels in the range of 310-564 pg/dl (normal range 10-65) and absence of signs of Albright hereditary osteodystrophy.Molecular studies: WES showed no pathogenic, likely pathogenic or variants of unknown significance in any known calcium-associated genetic disorder but a bi-allelic variant in the PTH itself (PTH, exon3: c.128G>A, p.Gly43Glu). This was confirmed by Sanger sequencing in the patient and her affected brothers.Because the patient's HypoCa was not controlled on large doses of calcitriol and calcium carbonate, a trial of teriparatide 20 mcg SC daily was started and resulted in normalization of calcium, decline in PTH levels and significant improvement in her general wellbeing.High PTH in the presence of congenital hypocalcemia is not always due to receptor or post-receptor defect and can be due to a biologically inactive mutated PTH. In such cases, treatment with teriparatide may result in stabilization of biochemical profile and improvement in quality of life.